Penegakan Hukum terhadap Praktik Destructive Fishing pada Perairan Lampung - Naomi Maynarti Hutagalung; Maroni Maroni; Maya Shafira; Diah Gustiniati Maulani; Muhammad Farid (Penerbit Goodwood, 2025)
Purpose: This study analyses law enforcement against destructive fishing practices in Lampung waters and the factors that can hinder it. Methodology: The research used a normative juridical approach and was supported by an empirical juridical approach. Primary and secondary data were used. Primary data are sourced from interviews, and secondary data are sourced from books, research results, and journals. Results: The study found that law enforcement against destructive fishing in Lampung involves three stages: formulation through relevant laws; implementation by the police with pre-emptive, preventive, and repressive actions; and execution through the punishment of offenders. Obstacles to enforcement include weak legal frameworks, reliance on Emergency Law Number 12 of 1951, limited patrol boats, lack of forensic laboratories, and low public legal awareness. These challenges have contributed to the continued prevalence of destructive fishing and have hindered effective law enforcement. Limitations: This research is limited to law enforcement against destructive fishing practices in Lampung waters and the factors that hinder it. Contribution: This research can be an educational tool for analysing law enforcement against destructive fishing practices in Lampung waters and the factors that hinder it.